Bees on the run: Nosema spp. (Microsporidia) in Apis mellifera and related products, Italy - Sgroi, Giovanni; D’Auria, Luigi Jacopo; Lucibelli, Maria Gabriella; Mancusi, Andrea; Proroga, Yolande Thérèsa Rose; Esposito, Mauro; Rea, Simona; Signorelli, Daniel; Gargano, Federica; D’Alessio, Nicola; Manoj, Ranju Ravindran Santhakumari; Khademi, Peyman; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThe decline of the European/western honeybee (Apis mellifera) population is on account of a plethora of microorganisms, such as Nosema apis and Nosema ceranae, two microsporidian fungi responsible of nosemosis that affects welfare and production of the bee industry. Accordingly, this study aimed to investigate the presence of both pathogens in bees, pollen and honey from apiaries in Southwestern Italy.MethodsFrom March to July 2022 and 2023, apiaries (n = 10) were selected and classified as High Impact Areas (HIAs, n = 5) and Low Impact Areas (LIAs, n = 5) according to a 5-point environmental risk index based on factors affecting bee health sand related productions. Bee, pollen and honey samples, were collected and tested for Nosema spp. DNA by specific PCR protocols targeting the 16S rRNA gene. Signs/symptoms of nosemosis were monitored and collected by the cooperation of beekeepers.ResultsOut of 10 apiaries, 6 (i.e., 60%, 95% CI: 31.3–83.2) tested positive for at least one sample to Nosema spp. DNA, being 2 positives for N. apis, 2 for N. ceranae and 2 co-infected (i.e., 20%, 5.7–51.0). Based on the biological samples, honey was positive for N. apis in one apiary, pollen for N. ceranae in two apiaries, and bees for N. apis in 3 apiaries, N. ceranae in 1 apiary, and both species in 1 apiary. In all the apiaries positive to N. apis and N. ceranae, high mortality and low honey production were observed. A higher risk of infection was observed in apiaries from HIAs (OR = 6.00). The sequences of N. apis and N. ceranae had 99.5–100% homology with those in the GenBank database. Whereas all sequences of N. apis were identical to each other, four sequences types of N. ceranae characterized by single nucleotide polymorphisms (SNPs) were identified. The computation of polymorphisms revealed high haplotype diversity (i.e., Hd = 1.000) and low nucleotide diversity (i.e., Pi = 0.00913) of N. ceranae sequence types.DiscussionThis study reveals a high circulation of N. apis and N. ceranae in Southwestern Italy, indicating the need for improved monitoring of these microsporidia to protect bee welfare and bee industry.